Pandangan Ulama tentang Kepemimpinan dalam Negara Islam - Arsyad Sobby Kesuma (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2009)
The idea of Islamic state and leadership has long been a subject of debate. But it remains intriguing to ask once and again what does Islamic state mean and what is its real and true nature? What does leadership mean and does Islam really need politics? This paper is designed mainly to answer these important questions. It will trace the ideal form of politics in Islam by investigating the formulas promulgated by the ulama over centuries. Two notions will be the focus of this investigation. First is the notion of how a leader should be elected, and second is the problem of what are the conditions of the leader. These two interrelated problems are at the centre of the idea of leadership in Islam. We argue that by understanding them one would necessarily be able to grasp the ?Islamic? formula of statehood and politics.